Eficacia del aspirado y secado, frente al lavado peritoneal en peritonitis secundaria. Hospital Víctor Lazarte Echegaray - León Fernández, Róger Martin (2020)
To determine the efficacy of aspiration and drying against peritoneal lavage in post operated secondary peritonitis patients. In such a way that under physiological and statistical support, we use the best cleaning technique of the peritoneal cavity in such cases. Background: For more than a century, surgeons have tried to reduce the morbidity and mortality rate of patients with peritonitis, devising local or systemic treatments, among which peritoneal lavage has played a preponderant role in the initial infectious control. However, the risks of irrigation with large amounts of fluid in the peritoneal cavity as a cleaning mechanism have been discussed on multiple occasions. Method: The operative report of each patient operated on for Generalized Peritonitis will be carefully reviewed, according to inclusion criteria, the relevant data of the operative finding and the procedure performed will be taken, and then data on how many and who developed complications or not, according to the procedure performed.